Strategic Management Practices and Organizational Performance: A Review of Empirical Studies - Taranpreet Kaur; Sakshi Gupta; Neha Bhagat (AG Volumes, 2025)
The paper is a review of the practices of strategic management and its effect on organizational performance, which synthesizes the empirical research in different fields. It discusses major practices like strategic planning, environmental scanning, strategy formulation and implementation, and strategic control, as this will reveal how the practices can be used to improve non-financial, financial, and operational performance. The review makes it clear that good strategic management helps organizations to match internal strengths and external opportunities, innovate and develop sustainable competitive advantage. Empirical findings always show that there is a positive correlation between the structured strategic management practices and organization performance with also the moderating role of the leadership, organizational culture, resource, and the environmental dynamics are also demonstrated.